Evaluasi Usability dengan Menerapkan Metode Heuristic Evaluation pada Website Dinas Pendidikan Kota Batu - Heraspati Yudha Pratama; Buce Trias Hanggara; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
The Batu City Education Office website is a website that provides a means of publishing and providing information and general descriptions regarding the Batu City Education Office. Based on the Regulation of the Minister of Communication and Information of the Republic of Indonesia Number 32 of 2017 concerning the Implementation of Portals and Websites of Government Agencies in Chapter X Monitoring and Evaluation Article 19 Paragraph (3) states